Features and factors of professional self-fulfillment of skilled people - Kokun, Oleg M. (Social Welfare: Interdisciplinary Approach, 2014)
The objective tendencies of social development determine significantly increased attention to the problem of persons’ self-fulfillment. Lack of knowledge on this phenomenon dictates the need for its theoretical justification as well as for empirical studies. This paper presents the results of a research aimed at determination of features and factors of professional self-fulfillment of skilled people of different ages and professions.
Keywords: self-fulfllment; professional self-fulfllment; professional development; factors of self-fulfllment; self-fulfllment attributes